The implication of the polymorphism of COX-1, UGT1A6, and CYP2C9 among cardiovascular disease (CVD) patients treated with aspirin / Nur Jalinna Abdul Jalil - Abdul Jalil, Nur Jalinna (2014)
Acetylsalicylic acid (ASA) or aspirin is a pro-drug of salicylates which has significant effect in reducing the cardiovascular events. Potential polymorphic enzymes responsible for the pharmacokinetic variations of ASA include cyclooxygenase-l (COX-1) UDP—glucuronosyltransferase (UGT1A6) and P450 (CYP) (CYP2C9). The main objective of this study is to determine the types and frequencies of variants of genes encoding COX-1 (A-842G), UGT1A6 (UGT1A6*2; A541G and UGT1A6*3; A522C and CYP2C9 (CYP2C9*3; A1075C) in the three major ethnic groups in Malaysian population (Malays, Chinese and Indian). The relevance of those polymorphisms in patients with cardiovascular disease was investigated. The project was approved by relevant Research Ethics Committee, A total of 165 patients with cardiovascular disease who were treated with 75-150 mg daily dose of aspirin and 300 healthy volunteer participants were recruited. DNA was extracted from the blood samples and genotyped for the single nucleotide polymorphisms (SNPs) using allele specific polymerase chain reaction (AS-PCR). All statistical analysis was performed using SPSS software version 2.0. P-values ≤ 0.05 were considered statistically significant. The association between genotype and adverse effect of aspirin therapy was estimated using odd ratio (OR). For UGT1A6, the pair-wise of both SNPs linkage disequilibrium (LD) was computed using Haploview. The variants frequencies for UGT1A6*2,*3 and CYP2C9*3 were 22.83%, 30.0% and 6.50%, respectively; while COX-1 (A-842G) was absent. We found that the genotype for both polymorphisms in UGT1A6 and CYP2C9*3 were significantly different between Indians, Malays and Chinese ethnic. The level of bilirubin and triglyceride of patients with different genotypes of UGT1A6 and CYP2C9*3 were significantly different (p-value < 0.05), respectively. In addition, CYP2C9*3 was found associated with gastritis events with odd ratio (OR) 6.8 (95 % Cl: 1.39 — 33.19; P = 0.033), SNPs of A541G and A522C among the Indians show swung linkage disequilibrium with D‘ value of 1.0. This study had identified significant association of genetic polymorphisms of UGTIA6 and CYP2C9*3 with gastritis event, level of bilirubin and triglyceride, Screening of patients with defective genetic variants could be of relevance in the clinical setting in identifying patients at risk of aspirin induced adverse effect. However, a iiiandomized, clinical study of bigger sample size would be needed before it is translated m clinical routine.